A relação entre currículo, culturas escolares e conhecimento escolar de sociologia em três escolas do Ceará - Sousa Neto, Manoel Moreira (2014)
Sociology returned officially, in the last decade, to high schools across the country. Currently it is possible to perceive, through the analysis of official documents, there is no rigid curriculum structure for the implementation of the discipline throughout the country. This theme makes room for questioning about how scientific knowledge is constructed in schools and how it is apprehended by the agents responsible for its consolidation. The analysis proposed here aims to understand the process of construction and implementation of the curriculum of the discipline of sociology in three schools on the outskirts of the city of Fortaleza, Ceará. To operationalize this study, delivery of the hypothesis that the curriculum, that will guide the practice of the discipline, is constructed from external references, found in the following official documents: National Curriculum Guidelines and Collection School Learner (state curriculum matrices), in addition to teaching school books, and is operated from the social conditions responsible for the emergence of a specific school culture in each school unit analyzed, and the creation axiological principles to discipline by their teachers. Thus, to obtain the empirical data from this study, performed the analysis of official documents on the subject, namely: Political Pedagogical Project, Bylaws and Annual Plans. Besides the analysis of documents during the fieldwork, I conducted semi-structured interviews with eight teachers of the discipline, from the referred schools. From the exploratory research and experience reports of teachers, it was possible to identify a gap between the written curriculum and the teachers' pedagogical practice. This contradiction was motivated by the fact that there is a unified curriculum basis for discipline. What meant that other variables, such as the process of stocking the teachers, the distribution of time for discipline at the three middle schools, lack of teaching materials, the presence of teachers trained in another area and the valuesassigned to the discipline by teachers, become priority at the moment of implantation of discipline in schools.